The Effect of Project-Based Service Learning on Community Empowerment in Sustainable Environmental Management - Festus Evly R I Liow; Vongdy Xayavong; Manivone Keolavong (Yayasan Adra Karima Hubbi, 2025)
Background. Environmental sustainability has become a pressing global issue, demanding innovative educational interventions that directly engage communities. Project-Based Service Learning (PBSL) integrates academic learning with community service, fostering mutual growth and empowerment. Purpose. This study investigates the effect of PBSL on community empowerment within the context of sustainable environmental management. The objective is to assess how active participation in student-led environmental projects enhances local communities’ knowledge, attitudes, and practices regarding sustainable development. Employing a mixed-method approach, the research involved quasi-experimental design and participatory observation in three rural villages. Method. Quantitative data were collected through pre- and post-tests, while qualitative data came from focus group discussions and stakeholder interviews. Results. The results indicate significant improvements in environmental awareness, collaborative problem-solving skills, and long-term community engagement. Furthermore, communities reported an increased capacity to manage environmental resources independently. Conclusion. In conclusion, PBSL not only serves as an effective pedagogical strategy but also empowers communities to take ownership of sustainable practices. The findings contribute to the growing literature on experiential learning and its transformative impact on society.